Effects of Empagliflozin and Dapagliflozin in alleviating cardiac fibrosis through SIRT6-mediated oxidative stress reduction - Hong-xia Ma; Ke Wu; Fei-hong Dong; Bing-kun Cai; Di Wu; Hui-yi Lu (Scientific Reports)
Abstract Sodium-glucose co-transport protein 2 (SGLT2) inhibitors, a novel category of oral hypoglycemic agents, offer a promising outlook for individuals experiencing heart failure with reduced ejection fraction. Evidence is emerging that highlights their potential in alleviating myocardial fibrosis and oxidative stress. However, the precise mechanisms through which SGLT2 inhibitors influence myocardial fibrosis induced by angiotensin II (Ang II) or transforming growth factor-β1 (TGF-β1) are not fully understood. This study aims to explore the intricate mechanisms by which SGLT2 inhibitors ameliorate myocardial fibrosis, particularly focusing on the nuanced interplay within the SIRT6 signaling pathway. Primary cardiac fibroblasts were isolated from the hearts of 1-3-day-old neonatal KM mice, were stimulated with Ang II or TGF-β1 to establish an in vitro model of myocardial fibrosis. Treatment with 10 µM Empagliflozin (EMPA) and Dapagliflozin (DAPA) significantly curtailed the proliferation of cardiac fibroblasts, substantially reduced collagen expression induced by Ang II/TGF-β1, and mitigated the phenotypic transformation and oxidative stress response. SIRT6, which is closely associated with myocardial fibrosis, demonstrated that the suppression its expression attenuated the protective effects of EMPA and DAPA against myocardial fibrosis and oxidative stress. Our findings suggest that SGLT2 inhibitors markedly decrease the Ang II/TGF-β1-induced transformation of cardiac fibroblasts to a myofibroblast phenotype by upregulating SIRT6 protein expression, thereby inhibiting oxidative stress and ameliorating myocardial fibrosis.